1988
DOI: 10.1099/0022-1317-69-5-999
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Defective Interfering Particles of Sonchus Yellow Net Virus from Chronically Infected Plants

Abstract: SUMMARYNicotiana edwardsonii plants were examined by electron microscopy 5 months after inoculation with Sonchus yellow net virus (SYNV). No virions were observed in leaf or root cells, but cells in sections of calyx tissue contained large numbers of virus particles. Most of these particles were only 73 to 86 ~ as tong as particles of standard SYNV. Nicotiana edwardsonii inoculated with sap extracted from chronically infected calyx became systemically infected but exhibited chlorotic mottling, instead of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Virus spread within the host plant happens through cell-to-cell movement (via plasmodesmata) and long-distance movement mainly through phloem vessels ( Matthews, 1991 ; Stavolone et al, 2005 ). It is known that the time at which viruses move out of the inoculated leaf into the rest of the plant varies widely depending on factors such as host and virus species, age of the host, method of inoculation and abiotic constraints ( Jensen, 1973 ; Ismail and Milner, 1988 ). In this study, we showed that the lag time to symptoms appearance (the mean time for symptoms to appear in the first non-inoculated leaf) and rate of systemic spread (the time required for all the plants of an accession to exhibit systemic symptoms) of CaMV was affected by accession identity and WD.…”
Section: Discussionmentioning
confidence: 99%
“…Virus spread within the host plant happens through cell-to-cell movement (via plasmodesmata) and long-distance movement mainly through phloem vessels ( Matthews, 1991 ; Stavolone et al, 2005 ). It is known that the time at which viruses move out of the inoculated leaf into the rest of the plant varies widely depending on factors such as host and virus species, age of the host, method of inoculation and abiotic constraints ( Jensen, 1973 ; Ismail and Milner, 1988 ). In this study, we showed that the lag time to symptoms appearance (the mean time for symptoms to appear in the first non-inoculated leaf) and rate of systemic spread (the time required for all the plants of an accession to exhibit systemic symptoms) of CaMV was affected by accession identity and WD.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the time at which viruses move out of the inoculation site into the rest of the plant varies widely depending on factors such as host and virus species, age of the host, method of inoculation and the abiotic factors of the environment [78,79]. In accordance with our previous results [13], here we showed that the lag time of symptom appearance and the rate of systemic spread of CaMV varied across accessions, and were contrastingly affected by water deficit depending on accession.…”
Section: Virus Spread Into the Plant Is Affected By Water Deficitmentioning
confidence: 99%
“…(Graves et al, 1996, review) Tospovirus TSWV L RNA DI RNA Encodes polymerase protein (Nagata et al, 2000) M RNA D Virus Loss of viral envelope and probable loss of vector transmission (Nagata et al, 2000) PBNV L RNA D Virus Gowda et al (1998) Rhabdoviridae SYNV Ismail and Milner (1988) Bromoviridae AMV RNA3 D RNA Graves et al (1996) (Graves et al, 1996, review) RNAs 3 and 4 D Virus Loss of vector transmission and ability to infect roots (Graves et al, 1996, review) Pecluvirus PCV RNA2 D Virus Loss of vector transmission (Graves et al, 1996, review) Benyvirus BNYVV RNA2 D Virus Loss of vector transmission (Graves et al, 1996, review) Sobemovirus CfMV Central region DI RNA Makinen et al (2000) Group 2 Analysis of these plants revealed that the levels of p19 (suppressor of RNA silencing), the p22 (movement protein), and sg mRNA2 were reduced much more than the level of the genomic RNA replication proteins.…”
Section: B Modulation Of the Functions Of Viral Factorsmentioning
confidence: 99%